Research on area-efficient low-entropy masking scheme for AES - Jiuxing JIANG; Jiao HOU; Hai HUANG; Yuying ZHAO; Xinxin FENG (Tongxin xuebao)
Based on the rotating S-box masking (RSM) proposed by Nassar et al,a low-entropy masking scheme for the advanced encryption standard (AES) was proposed.Reducing the area complexity by reusing the S-boxes,improving the hardware security by shuffling operation and improving the throughput by pipelining operation were the main idea of the proposed scheme.For the AES,the number of S-boxes could be reduced from 16 to 4 (key expansion module wasn’t included).Compared with the RSM,the combinational logic,the dedicated logic and the memory size are reduced to 69%,60% and 80% respectively.In addition,the theoretical analysis shows that the proposed scheme can resist offset based CPA attack,thus has higher security than the RSM.